PERANAN KANTOR OTORITAS BANDAR UDARA WILAYAH VIII MANADO DALAM PENGENDALIAN KESELAMATAN PENERBANGAN DI BANDAR UDARA SAM RATULANGI MANADO - NGANTUNG, IGEL; RUMAPEA, PATAR; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2018)
The purpose of this research is to know the role of Airport Authority Officeof Regional VIIIManado in flight safety control. This study used qualitative research methods. There were 10 (ten)respondents who were taken from the leadership / officials and officers at the office of the Airport Authority(6 persons), the airline officer (2 persons), and the passenger of the plane (2 persons). Data were collectedby interview technique, while data analysis used qualitative analytical technique of interactive models fromMiles and Huberman. Based on the results of the research can be concluded: the role of the Office of AirportAuthority of Region VIII Manado in flight safety control can be seen through the main tasks and functionsand existing authorities. Manado Airport VIII Airport Authority Office as Technical Implementation Unitwithin the Directorate General of Civil Aviation responsible to the Director General of Civil Aviation. TheOffice of Manado Airport VIII Airport Authority establishes coordination and cooperation with othergovernment agencies, PT. Angkasa Pura, the airlines and various related parties. The function of the Officeof Manado Airport VIII Airport Authority is 11 (eleven) functions as a form of duties implementation, someof which are implementing the regulation, control and supervision of security and safety as well as smoothflight and carry out coordination and facilitation of activities of government functions and service of airportand services flights and operational smoothness at Sam Ratulangi Airport Manado.Password : role, airports authority, control, safety flight.